Smoking status informs about the risk of advanced serrated polyps in a screening population - IJspeert, J. E. G.; Bossuyt, P. M.; Kuipers, E. J.; Stegeman, I.; de Wijkerslooth, T. R.; Stoop, E. M.; van Leerdam, M. E.; Dekker, E. (Endoscopy International Open, 2016)
Background and study aims: Evidence has accumulated that approximately 15 % to 30 % of colorectal cancers (CRC) arise from serrated polyps (SP). Population screening, therefore, should be designated to detect advanced SP, in addition to advanced adenomas and CRC. We aimed to evaluate whether CRC risk factors also act as risk factors for advanced SP.Patients and methods: Data were collected in the colonoscopy arm of a multicenter randomized trial comparing colonoscopy with CT-colonography for primary population screening. Information on risk factors was obtained by screening participants before colonoscopy with a validated risk questionnaire. Advanced SP were defined as SP ≥ 10 mm and/or with dysplasia. Endoscopists were instructed to resect all detected lesions. Odds ratios (OR) for the detection of advanced SP as most advanced lesion were calculated using multiple logistic regression analysis.Results: Of 6 600 invited participants, 1 426 underwent a colonoscopy and 1 236 also completed the questionnaire. In 40 participants an advanced SP was the most advanced lesion detected. Multivariate analysis demonstrated a strong association between current smoking and the presence of at least one advanced SP (OR 4.50; 95 % CI 2.23 – 8.89; P < 0.001). A significant association was also demonstrated for higher fiber intake (OR 1.36 per 20 gram intake; CI 1.07 – 1.73; P = 0.01). Other clinical CRC risk factors did not show a significant association with the presence of at least one advanced SP in the univariate analyses. Fecal haemoglobin levels were also not significantly associated with the presence of advanced SPs (OR 1.00 per 10 ng/mL CI 0.97 – 1.03, P = 0.99).Conclusions: Current smoking is a strong clinical risk factor for the presence of advanced SPs. As such, smoking status could contribute to risk stratification in targeted CRC population screening.Dutch Trial Register: NTR1829 (www.trialregister.nl)